Artemis‐dependent DNA double‐strand break formation at stalled replication forks. Issue 6 (15th April 2013) - Unno, Junya; Takagi, Masatoshi; Piao, Jinhua; Sugimoto, Masataka; Honda, Fumiko; Maeda, Daisuke; Masutani, Mitsuko; Kiyono, Tohru; Watanabe, Fumiaki; Morio, Tomohiro; Teraoka, Hirobumi; Mizutani, Shuki
<x xml:space="preserve">Abstract</x> Stalled replication forks undergo DNA double‐strand breaks (DSBs) under certain conditions. However, the precise mechanism underlying DSB induction and the cellular response to persistent replication fork stalling are not fully understood. Here we show that, in response to hydroxyurea exposure, DSBs are generated in an Artemis nuclease‐dependent manner following prolonged stalling with subsequent activation of the ataxia–telangiectasia mutated (ATM) signaling pathway. The kinase activity of the catalytic subunit of the DNA‐dependent protein kinase, a prerequisite for stimulation of the endonuclease activity of Artemis, is also required for DSB generation and subsequent ATM activation. Our findings indicate a novel function of Artemis as a molecular switch that converts stalled replication forks harboring single‐stranded gap DNA lesions into DSBs, thereby activating the ATM signaling pathway following prolonged replication fork stalling.